PRAKTIK TA’AWUN DALAM RUMAH TANGGA: PEREMPUAN SEBAGAI PENANGGUNG JAWAB EKONOMI KELUARGA DI DESA SUMBERJAMBE - Ihsan, Zuhdan; Kumaini, Ruston (USRAH: Jurnal Hukum Keluarga Islam, 2025)
The shifting structure of roles within households continues to evolve alongside the growing involvement of women in sustaining the family's financial needs. This study explores how the Islamic value of ta’awun underpins women’s active participation as primary economic providers within the nuclear family. It aims to portray the lived experiences of women engaged in both informal and formal sectors while interpreting the dual-role dynamics they encounter daily. A mixed-methods approach was employed, combining in-depth interviews, participatory observation, and quantitative data from questionnaires. Contributing factors include financial pressure, the need for self-actualization, and inadequate spousal support—each contributing to dual-role burdens and relational tensions. From an Islamic standpoint, this involvement is considered religiously legitimate and embodies a cooperative spirit rooted in blessing. The findings highlight a transformation in gender roles within the family and emphasize the importance of spiritual values in harmonizing domestic and public responsibilities. Furthermore, the study is expected to provide a foundation for developing family policies that are more responsive to the realities faced by women in contemporary society. Keywords: ta’awun, gender roles, working women, nuclear family, spiritual values Abstrak Perubahan struktur peran dalam rumah tangga terus berkembang seiring dengan meningkatnya partisipasi perempuan dalam menopang kebutuhan ekonomi keluarga. Fokus utama dalam studi ini adalah bagaimana nilai ta’awun menjadi dasar keterlibatan perempuan sebagai penanggung jawab ekonomi dalam lingkup keluarga inti. Penelitian ini bertujuan untuk menggambarkan realitas perempuan yang bekerja di sektor informal dan formal serta menafsirkan dinamika peran ganda yang mereka hadapi dalam keseharian. Pendekatan mixed methods digunakan, memadukan wawancara mendalam, observasi partisipatif, serta data kuantitatif dari angket. Faktor-faktor pendorong di antaranya tekanan finansial, kebutuhan aktualisasi diri, dan lemahnya dukungan pasangan, yang turut menghadirkan tantangan berupa beban peran ganda dan ketegangan relasional. Keterlibatan ini, dalam perspektif Islam, dipandang sah secara syar’i dan mencerminkan nilai kerja sama yang berlandaskan keberkahan. Hasil penelitian menyoroti pergeseran peran gender dalam keluarga serta pentingnya penguatan nilai spiritual dalam membangun harmoni antara tanggung jawab domestik dan publik. Temuan ini juga diharapkan dapat menjadi landasan dalam penyusunan kebijakan keluarga yang lebih responsif terhadap kondisi perempuan di era kontemporer.